Relationship among nephron number, cortical volume, and glomerular pressure in healthy kidney donors - Hiroki Nobayashi; Go Kanzaki; Takaya Sasaki; Rina Oba; Yusuke Okabayashi; Kotaro Haruhara; Kentaro Koike; Akimitsu Kobayashi; Izumi Yamamoto; Nobuo Tsuboi; Takashi Yokoo (Physiological Reports)
Abstract Glomerular hypertension is a critical factor in kidney disease progression. Traditionally, nephron number (Nglom) was considered a determinant of glomerular hemodynamics, but emerging evidence suggests a more substantial impact of renal structural factors. This cross‐sectional study aimed to evaluate the relationship between renal histopathological parameters and intraglomerular hydrostatic pressure (Pglo) in healthy donors. Retrospective analyses were conducted on 60 healthy living donors who donated a kidney between January 1, 2007, and September 30, 2022. The non‐sclerotic glomerular number (NglomNSG), glomerular volume, cortical volume, and other histopathological parameters were evaluated. Pglo was estimated using Gomez's equation. Pglo was positively associated with cortical volume (standardized regression coefficient [β] = 0.34, p = 0.04) but not with NglomNSG (β = 0.12, p = 0.44). Cortical volume was inversely associated with afferent arteriolar resistance (β = −0.33, p < 0.01). These findings suggest that an increase in cortical volume, independent of nephron number, may contribute to an increase in Pglo through a reduction in afferent arteriolar resistance. These results refine current models of glomerular hemodynamics, highlighting the importance of structural renal evaluation, including cortical volume, in assessing early chronic kidney disease risk.